2014
DOI: 10.1107/s2053230x14001514
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of the N-terminal regulatory domain of the enhancer-binding protein FleQ fromStenotrophomonas maltophilia

Abstract: FleQ is a master regulator that controls bacterial flagellar gene expression. It is a unique enhancer-binding protein or repressor protein comprising an N-terminal FleQ domain, an AAA(+)/ATPase σ54-interaction domain and a helix-turn-helix DNA-binding domain. FleN is a putative ATPase with a deviant Walker A motif that works together with FleQ by binding to the FleQ N-terminal domain to fully express pel, psl and cdr operons in the presence of c-di-GMP to enhance biofilm formation. Stenotrophomonas maltophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…In addition, the genes encoding three transcription regulators ( fleQ , fsnR , and bfmA ) also control biofilm development. FleQ binds to the putative ATPase FleN to form a complex that directs flagellar gene expression 30 . FsnR, designated as a response regulator with transcription-regulating activity, binds directly to the promoter regions of gene clusters involved in flagellar assembly to activate their transcriptional initiation 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the genes encoding three transcription regulators ( fleQ , fsnR , and bfmA ) also control biofilm development. FleQ binds to the putative ATPase FleN to form a complex that directs flagellar gene expression 30 . FsnR, designated as a response regulator with transcription-regulating activity, binds directly to the promoter regions of gene clusters involved in flagellar assembly to activate their transcriptional initiation 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…All these genes were located on the chromosome. Genes responsible for polysaccharide production ( spgM , rmlA , and rmlC ) ( Huang et al., 2006 ; Pompilio et al., 2011 ; Zhuo et al., 2014 ; Madi et al., 2016 ), quorum sensing (QS) ( rpfF , ax21 , and smoR ) ( Bahar et al., 2014 ; Devos et al., 2015 ; García et al., 2015 ; Huedo et al., 2015 ; Martínez et al., 2015 ; Ryan et al., 2015 ; Huedo et al., 2018 ), and flagella ( fleQ , flgE/G/G/K/I , flhA, fliF/I/K/M/N/O/A , and fimV ) ( Roscetto et al., 2012 ; Yang et al., 2014 ; Kang et al., 2015 ; Liu et al., 2017 ; Kim et al., 2018 ) were identified in S. maltophilia SMYN41–SMYN45 ( Flores-Treviño et al., 2019 ). Several other biofilm-related genes ( purE/D/C/I , guaA , and ravS ) were annotated in the five strains ( Kang et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“… Yang et al (2014) reported that flagellar gene expression in S. maltophilia is controlled by FleQ (Smlt2295). This transcriptional regulator, an enhancer-binding protein, is homologous to the similar master regulator in P. aeruginosa and it is the major target for the c-di-GMP produced by the wrinkly spreader phenotype (Wsp) chemosensory system pathway ( Hickman et al, 2005 ; Yang et al, 2014 ). FleQ works together with a putative ATPase, FleN, and is inhibited by binding c-di-GMP.…”
Section: Flagellamentioning
confidence: 99%
“…FleQ works together with a putative ATPase, FleN, and is inhibited by binding c-di-GMP. Inhibition of this complex and, therefore, Wsp pathway activation results in elevated expression of biofilm-associated pel , psl, and cdr operons and a reduction of flagellar gene expression ( Hickman et al, 2005 ; Hickman and Harwood, 2008 ; Yang et al, 2014 ). The situation is reversed if the concentration of c-di-GMP is low: FleQ remains unbounded, and it leads to increased expression of flagellar genes, and, therefore, the ability of bacteria to be sessile in biofilms decreases.…”
Section: Flagellamentioning
confidence: 99%